Extravagant abjection blackness, power, and sexuality in the African American literary imagination - Scott, Darieck (New York University Press, 2010)
Summary: Challenging the conception of empowerment associated with the Black Power Movement and its political and intellectual legacies, this title contends that power can be found not only in martial resistance, but, surprisingly, where the black body has been inflicted with harm or humiliation.